Calcium-Free and Cytochalasin B Treatment Inhibits Blastomere Fusion in 2-Cell Stage Embryos for the Generation of Floxed Mice via Sequential Electroporation - Takuro Horii; Ryosuke Kobayashi; Mika Kimura; Sumiyo Morita; Izuho Hatada (Cells, 2020)
The generation of conditional knockout mice using the Cre-loxP system is advantageous for the functional analysis of genes. Flanked by two loxP sites (floxed) mice can be directly obtained from fertilized eggs by the CRISPR/Cas9 genome editing system. We previously reported that sequential knock-in (KI) of each loxP site by electroporation (EP) at the 1- and 2-cell embryonic stages increases the number of mice with floxed alleles compared with simultaneous KI. However, EP at the 2-cell stage frequently induced blastomere fusion. These fused embryos cannot develop to term because they are tetraploidized. In this study, we examined the following three conditions to inhibit blastomere fusion by EP at the 2-cell stage: (1) hypertonic treatment, (2) Calcium (Ca2+)-free treatment, and (3) actin polymerization inhibition. Hypertonic treatment of 2-cell stage embryos prevented blastomere fusion and facilitated blastocyst development; however, KI efficiency was decreased. Ca2+-free treatment and actin polymerization inhibition by cytochalasin B (CB) reduced fusion rate, and did not have negative effects on development and KI efficiency. These results suggest that Ca2+-free and CB treatment at the 2-cell stage is effective to generate floxed mice in combination with a sequential EP method.